Spectrum of Interstitial Lung Disease Patterns in Connective Tissue Diseases and their Outcomes: a Retrospective Analysis - Amar Lal; Muhammad Ahmed Saeed; Muhammad Rafaqat Hameed; Maryam Aamer; Umbreen Arshad; Hiba Shariq (Pakistan Armed Forces Medical Journal, 2026)
Objective: To evaluate patterns of connective tissue disease-associated interstitial lung disease and to evaluate disease outcomes across various CTD subtypes in a tertiary care setting in Lahore, Pakistan.Study Design: Observational Retrospective StudyPlace and Duration of the Study: Rheumatology Department, Central Park Teaching Hospital, and its affiliated Clinics, Lahore, Pakistan, from 2021 to 2025.Methodology: The data of 174 patients diagnosed with CTD-ILD was reviewed. Inclusion criteria included adult patients with a confirmed CTD diagnosis (as per ACR/EULAR criteria) and HRCT-confirmed ILD. Data on demographics, serology, HRCT patterns, and pulmonary function tests (PFTs), and outcomes were analyzed using SPSS v27. The statistical significance was set at p ≤ 0.05.Results: Among 174 patients, 93.7% were female, with a mean age of 49.4 ± 13.7 years. The most common CTD was systemic sclerosis (30.5%), followed by rheumatoid arthritis (21.8%) and mixed connective tissue disease (MCTD) (19.5%). NSIP was the predominant HRCT pattern (61.5%), followed by UIP (23.0%). Disease activity varied, with active disease most common in SLE (62.5%) and systemic sclerosis (47.2%). PFTs showed moderate to severe restriction in a majority of patients, particularly those with myositis, systemic sclerosis, and SLE (p < 0.001).Conclusion: CTD-ILD presents with heterogeneous clinical, serological, and radiological profiles. NSIP is the most frequent ILD pattern across CTDs. Timely identification of ILD patterns and targeted immunosuppressive therapy may improve patient outcomes.